Abstract ID: 143 Monte Carlo simulation tool for online treatment monitoring in hadrontherapy with in-beam PET. (October 2017) - Fiorina, Elisa; Ferrero, Veronica; Pennazio, Francesco; Baroni, Guido; Battistoni, Giuseppe; Belcari, Nicola; Bisogni, Maria Giuseppina; Camarlinghi, Niccolò; Cerello, Piergiorgio; Ciocca, Mario; Del Guerra, Alberto; Donetti, Marco; et al.
Abstract : Hadrontherapy permits treating cancer with very conformable dose distributions and increased radiobiological effects. Monitoring systems to verify particle range while treating are needed to fully exploit these advantages. The INSIDE project aims at building a bimodal system to acquire photons, coming from positron annihilations, and prompt charge particles related to the beam position inside patients[1] . In January 2016, the in-beam PET detector was installed at the Italian Center of Oncological Hadrontherapy (CNAO) and characterized with phantoms[2, 3] . In December 2016, the INSIDE in-beam PET monitored two consecutive treatment sessions with protons on its first patient. In-beam PET images must be compared with an expected prior image, therefore a FLUKA-based[4, 5] simulation tool has been developed. The framework includes the simulations of the patient/phantom, the detector, the beam line and temporal structure. The beam delivery follows either the treatment plan or the measurements from the Dose Delivery System and the detector geometry and resolution are taken into account. During the characterization phase, a good agreement between measurements and simulations was found[2, 3] . Preliminary results on the first patient treatments indicate that after about two minutes of a four-minutes long irradiation the PET image has significant statistics to be compared with the prior image. During the 2017, the INSIDE in-beam PET system and simulation tool will be further tested in-vivo and optimized for clinical routine.